Training Manajemen Pengelola Air Bersih melalui Edukasi Inovatif pada Dokter Kecil Sekolah Dasar - Eram Tunggul Pawenang; Yuni wijayanti; Arum Siwiendrayanti; Weni Apriyani; Reza Adi Setiawan; Salma Al Huda (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2025)
Knowledge about clean water is crucial to instill in elementary school students from an early age. Elementary school students at Sekaran 02 Elementary School in Semarang City still lack understanding and knowledge about clean water and clean water management. There have been no outreach activities about clean water and clean water management at the school. The purpose of this community service activity is to improve elementary school students' understanding of clean water, as well as equip them with practical skills in managing and checking water quality simply. The solution offered by this community service activity is in the form of outreach about clean water and clean water management training. The methods used are lectures, demonstrations, and direct practice of clean water management. Instruments used include modules, leaflets, and short videos. The target and expected output is an increase in the knowledge and skills of students at Sekaran 02 Elementary School in Semarang City about clean water and how to manage clean water simply.